2015
DOI: 10.11648/j.ijefm.20150305.20
|View full text |Cite
|
Sign up to set email alerts
|

Social Media as a Factor for Promoting Entrepreneurship - the Middle East & Oman Scenario

Abstract: This study is focusing on to establish the Social Media as a factor for promoting entrepreneurship in Oman & the Middle East region. This was done by social media in general public as well as by Businesses & entrepreneurs. The results generated based on the social media usage in Oman and Middle East with respect to Facebook, Twitter, LinkedIn, Instagram. In terms of theoretical survey, this article clearly explains that all nations, aside from that these countries had more than 90% of their populace utilizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…showed that e-commerce spurs entrepreneurship in urban and rural areas in two ways, encouraging the start of new businesses and reducing the exit of existing businesses from the market. Social media is also used to promote entrepreneurship by entrepreneurs (Samuel and Sarprasatha, 2015). Besides that, the role of other media such as tv, online media, print media and influencers also supports the development of regional entrepreneurship.…”
Section: Information Mediamentioning
confidence: 99%
“…showed that e-commerce spurs entrepreneurship in urban and rural areas in two ways, encouraging the start of new businesses and reducing the exit of existing businesses from the market. Social media is also used to promote entrepreneurship by entrepreneurs (Samuel and Sarprasatha, 2015). Besides that, the role of other media such as tv, online media, print media and influencers also supports the development of regional entrepreneurship.…”
Section: Information Mediamentioning
confidence: 99%